2015
DOI: 10.1089/pho.2015.3926
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage of Self-Etch Adhesive System in Class V Cavities Prepared by Using Er:YAG Laser with Different Pulse Modes

Abstract: These observations indicate that the micro-irregularities of the cementum surface could facilitate the formation of a hybridization zone with a self-etch adhesive system. Therefore, the microleakage of Er:YAG laser irradiation was significantly decreased compared with diamond bur cavities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…According to this study, an equal amount of microleakage occurs when an etchand-rinse adhesive is used on dentinal margins either on conventional cavity preparation or on a laser-prepared cavity. For the self-etch systems, the same authors are reporting less microleakage for laser preparations 10 and this is in compliance with the findings of two other studies 37,43 . A possible explanation of less microleakage could be that laser alterations on dentin surfaces leave micro-irregularities and no smear layer.…”
Section: Discussionsupporting
confidence: 86%
“…According to this study, an equal amount of microleakage occurs when an etchand-rinse adhesive is used on dentinal margins either on conventional cavity preparation or on a laser-prepared cavity. For the self-etch systems, the same authors are reporting less microleakage for laser preparations 10 and this is in compliance with the findings of two other studies 37,43 . A possible explanation of less microleakage could be that laser alterations on dentin surfaces leave micro-irregularities and no smear layer.…”
Section: Discussionsupporting
confidence: 86%
“…Minimum microleakage was associated with an energy density of 3.77 J/cm 2 on both the occlusal and gingival cementum margin. 44 A similar conclusion was reported for erbium, chromium, yttrium, scandium, gallium, and garnet (Er,Cr:YSGG) used in Class V cavities of primary teeth with nanofilled resinmodified glass ionomer restorations. 45 However, some studies showed no significant difference in microleakage between cavities prepared by laser (Er:YAG and Er,Cr:YSGG) and diamond rotary instruments .…”
Section: Potential Applications Of Clinical Techniques Cavity Preparasupporting
confidence: 63%
“…This study, while still correlating with those researching the effects of microleakage is very novel in its purpose not only to analyze the adhesive or bonding strength in vitro, as was the original goal of other researchers and/or manufacturers of such materials, but also to study the microleakage of the adhesive materials, which is one of the less-trialed factors, directly concerning long-term reliability, often leading to multiple dental diseases [14]. It is important to note that other dye-leakage studies have mostly evaluated the leakage level by degrees only [15][16][17][18], while Phanombualert et al [19] also offered measurements in micrometers. This study combines both.…”
Section: Introductionmentioning
confidence: 99%